Quantitative Characterization of Pore Space for the Occurrence of Continental Shale Oil in Lithofacies of Different Types: Middle Jurassic Lianggaoshan Formation in Southeastern Sichuan Basin of the Upper Yangtze Area - Xiangfeng Wei; Kun Zhang; Qianwen Li; Dongfeng Hu; Zhihong Wei; Ruobing Liu; Zhujiang Liu; Jiayi Liu (Geofluids)
In addition to marine and marine-continental transitional strata, the continental ones are also widely distributed in various oil and gas-bearing basins in China. The continental shale generally provides favorable material bases for hydrocarbon generation, such as wide distribution, large thickness, multiple series of strata, high TOC content, nice organic matter type, and moderate thermal evolution. Part of such shale contains shale oil, but the pore space characteristics for the occurrence of this oil are not thoroughly studied. In order to accurately and quantitatively characterize the pore space where the continental shale oil in different types of lithofacies occurs, we sampled the rock cores from the Middle Jurassic Lianggaoshan Formation in the southeastern Sichuan Basin of the Upper Yangtze Area. The TOC content and mineral composition were analyzed, and we also carried out experiments on CO2 and N2 adsorptions, high-pressure mercury injection, and wash oil. Results show significant differences in pore space characteristics for the occurrence of shale oil in different types of lithofacies. In organic-rich mixed and clayey mudstones with the highest TOC content, the free shale oil, occupying the largest reservoir space, mainly occurs in macropores and mesopores, and the adsorbed shale oil, occupying the largest reservoir space, mainly occurs in mesopores. In the organic-bearing clayey mudstone, which has a higher TOC content, the free shale oil takes a larger reservoir space and mainly occurs in macropores, followed by mesopores, and the absorbed one, occupying a larger reservoir space, mostly occurs in micropores and then the mesopores. The organic-bearing mixed mudstone has a moderate TOC content, in which the free shale oil occupies a smaller reservoir space and primarily occurs in mesopores, followed by macropores, and the absorbed one, which takes a larger reservoir space, all occurs in mesopores. In the fine sandstone, the free shale oil occupies a smaller reservoir space and primarily occurs in mesopores, while the absorbed one occupies a smaller reservoir space and all occurs in mesopores.